PREDICTIVE FACTOR OF METASTATIC RENAL CELL CARCINOMA PATIENT IN SARDJITO HOSPITAL PERIOD 2010 - 2015 - Kohar, Moch Abdul; Tranggono, Untung (Indonesian Journal of Urology, 2018)
Objective: To analyze the association between various prognostic factors and the incidence of renal cell carcinoma (RCC) metastatic. Material & methods: This is a descriptive retrospective study. In this research, the dependent variable is metastatic RCC while the predictor factor as independent variable influencing renal cell carcinoma metastasis. The study population were all patients with renal cell carcinoma that were diagnose in Sardjito Hospital from period 2010 to 2015. Results: In this study there were 34 patients who became the object of research. Consisting of men as many as 20 people (58.8%) while women as many as 14 people (41.2%), while for the age category <51 years as many as 16 people (47.1%) while RCC patients aged > 51 years old 18 People (52.9%). In this study, patients with RCC mostly found in stage 2 were 15 people (44.1%), stage 3 of 6 people (17.6%), stage 4 were 13 people (38.2%). These results are consistent with previous studies which suggest that RCC is found most frequently in stage 2 (Soblin et al, 1997). The p value = < 0.038 indicates that there is a significant correlation between tumor staging and metastatic occurrence in RCC, the result of this study is similar to the previous study which stated that the higher the staging of the tumor the greater the risk of metastasis with p value = 0.001 (Vina et al., 2016). Conclusion: There was a significant association between staging of renal cancer and metastatic events.